Identification of novel SNPs of ovine PRL gene and their association with milk production traits - Ozmen, O.; Kul, S. (Pleiades Publishing Inc, 2016)
Prolactin (PRL) is a lactogenic hormone that plays a significant role in milk production; its depletion in sheep provokes a severe reduction of milk secretion. Thus, PRL also could be used as a positional marker gene associated with milk production and composition traits. Therefore, the purpose of the study was to identify genotype frequencies of single nucleotide polymorphisms the intron 2 in ovine PRL gene and its possible association genotypes with milk traits in dairy sheep breeds. The genetic structures of ovine PRL gene were examined by PCR-RFLP and DNA sequencing methods in three sheep populations. Four hundred and fifty blood and milk samples were used in the study, which included 150 samples from each of Sakiz, Akkaraman and Awassi ewes respectively. As a result, PRL genotype AA showed a strong association with milk yields content, whereas the animals carrying BB genotype had a higher fat percentage value in the three sheep breeds. Haplotype analysis of the obtained sequences showed the presence of 12 haplotypes in the PRL intron 2 region. In the present study, we have reported for the first time 48 SNPs of the PRL gene for intron 2 in dairy sheep breeds. These preliminary results indicate that the identified SNPs lend themselves readily for further research regarding physiological impacts such as milk production and reproductive traits in other dairy sheep populations.
Keywords: prolactin; sheep; milk production traits; SNPs